IgG antibody production and persistence to 6 months following SARS-CoV-2 vaccination: A Northern Ireland observational study. Issue 18 (20th April 2022) - Robertson, Louise J.; Price, Ruth; Moore, Julie S.; Curry, Grace; Farnan, John; Black, Amy; Blighe, Kevin; Nesbit, M. Andrew; McLaughlin, James A.D.; Moore, Tara
Abstract: Background: This study evaluates spike protein IgG antibody response following Oxford-AstraZeneca COVID-19 vaccination using the AbC-19™ lateral flow device. Methods: Plasma samples were collected from n = 111 individuals from Northern Ireland. The majority were >50 years old and/or clinically vulnerable. Samples were taken at five timepoints from pre-vaccination until 6-months post-first dose. Results: 20.3% of participants had detectable IgG responses pre-vaccination, indicating prior COVID-19. Antibodies were detected in 86.9% of participants three weeks after the first vaccine dose, falling to 74.7% immediately prior to the second dose, and rising to 99% three weeks post-second vaccine. At 6-months post-first dose, this decreased to 90.5%. At all timepoints, previously infected participants had significantly higher antibody levels than those not previously infected. Conclusion: This study demonstrates that strong anti-spike protein antibody responses are evoked in almost all individuals that receive two doses of Oxford-AstraZeneca vaccine, and which largely persist beyond six months after first vaccination.